2012
DOI: 10.1016/j.jacc.2011.09.070
|View full text |Cite
|
Sign up to set email alerts
|

A New Era in the Natural History of Dilated Cardiomyopathy

Abstract: A New Era in the Natural History of Dilated Cardiomyopathy I read with interest the paper by McNamara et al. (1), which supports the findings of our previous report of a logistic model that identifies factors associated with restoration of normal ventricular function in this patient population (2). As we noted in that paper, which indeed references the marked improvement in left ventricular function observed in the placebo group of the IMAC (Intervention in Myocarditis and Acute Cardiomyopathy) trial, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…After an adequate period of optimal medical therapy (almost 2 years), 15% of patients with DCM in our study showed apparent healing and more favorable long‐term outcomes. These findings are only partially surprising because they are consistent with the well‐known effectiveness of ACE inhibitors, β‐blockers, and aldosterone antagonists in inducing LV reverse remodeling in more than one third of patients with DCM at mid‐term 5 , 24 and subsequently higher long‐term survival directly related to the amount of LV systolic function and improvement in size ( Figure 1 ). Moreover, this study probably underestimated the magnitude of the apparent healing phenomenon.…”
Section: Discussionsupporting
confidence: 61%
“…After an adequate period of optimal medical therapy (almost 2 years), 15% of patients with DCM in our study showed apparent healing and more favorable long‐term outcomes. These findings are only partially surprising because they are consistent with the well‐known effectiveness of ACE inhibitors, β‐blockers, and aldosterone antagonists in inducing LV reverse remodeling in more than one third of patients with DCM at mid‐term 5 , 24 and subsequently higher long‐term survival directly related to the amount of LV systolic function and improvement in size ( Figure 1 ). Moreover, this study probably underestimated the magnitude of the apparent healing phenomenon.…”
Section: Discussionsupporting
confidence: 61%